2013
DOI: 10.1111/1574-6968.12152
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic amino acids as precursors of antimicrobial metabolites inGeotrichum candidum

Abstract: Geotrichum candidum ATCC 204307 was previously found to generate phenyllactic acid (PLA) and indoleacetic acid (ILA) in complex culture media. In this study, a relationship between concentrations of PLA, ILA, and hydroxy PLA (OH-PLA) and initial concentrations of phenylalanine, tryptophan, and tyrosine, added respectively as unique sources of nitrogen in synthetic medium, was established. Phenylpyruvic acid (PPA), an intermediate compound of PLA metabolism, was able to induce not only PLA but also phenylethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…No comparable study is available to reveal the antagonist activity of G. candidum against A. hydrophila in fish. However, in vivo antagonist activity against Staphylococcus aureus (Ibrar et al, 2017), as well as in vitro antimicrobial activity alone (Naz, Gueguen-Minerbe, Cretenet, & Vernoux, 2013;Samuel, Prince, & Prabakaran, 2017) or in mix culture with Enterococcus faecium (Ghori et al, 2018) Overall results of the present study showed that G. candidum-QAUGC01 alone has great potential to improve survival, growth rate, proximate composition of muscle and resistance to pathogen during early rearing of L. rohita. These positive effects may be ascribed to their morphological structure, higher enzymatic potential and immune-stimulatory effect.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…No comparable study is available to reveal the antagonist activity of G. candidum against A. hydrophila in fish. However, in vivo antagonist activity against Staphylococcus aureus (Ibrar et al, 2017), as well as in vitro antimicrobial activity alone (Naz, Gueguen-Minerbe, Cretenet, & Vernoux, 2013;Samuel, Prince, & Prabakaran, 2017) or in mix culture with Enterococcus faecium (Ghori et al, 2018) Overall results of the present study showed that G. candidum-QAUGC01 alone has great potential to improve survival, growth rate, proximate composition of muscle and resistance to pathogen during early rearing of L. rohita. These positive effects may be ascribed to their morphological structure, higher enzymatic potential and immune-stimulatory effect.…”
Section: Discussionmentioning
confidence: 59%
“…No comparable study is available to reveal the antagonist activity of G. candidum against A. hydrophila in fish. However, in vivo antagonist activity against Staphylococcus aureus (Ibrar et al, ), as well as in vitro antimicrobial activity alone (Naz, Gueguen‐Minerbe, Cretenet, & Vernoux, ; Samuel, Prince, & Prabakaran, ) or in mix culture with Enterococcus faecium (Ghori et al, ) against many pathogenic bacteria is well established. Moreover, like our results NavinChandran et al () reported low level antagonistic activity of B. cereus against A. hydrophila .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, finding cyclo(Tyr-Pro) containing one type of aromatic AA, tyrosine (Table 5), also seems to be caused by the use of the defined starter Ln. mesenteroides LBP-K06 because hydroxy phenyllactic acid produced from tyrosine has an antimicrobial spectrum as phenyllactic acid, particularly in starter kimchi (Crowleya et al, 2013; Naz et al, 2013). These results strongly imply that spontaneously fermented cabbage is likely to have a varied microflora, as seen in the very different chromatographic separation pattern and CDP production compared to starter kimchi (Figures 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Their active substances are involved in widely used pesticides in agriculture field (Anonymous 1). (Naz et al, 2013) and bacterial strains were cultivated on liquid medium Luria-Bertani (LB) at 37°C for 48 h according to Rahman et al (2012) with some modifications. These micro-organisms were incubated with shaking (120 rpm).…”
Section: Pesticidesmentioning
confidence: 99%